The association of non-motor symptoms with motor symptoms in parkinson’s disease (Annals of Medical Research, 2021)
Aim: Idiopathic Parkinson’s disease (IPD) is the second most common progressive neurodegenerative disorder and well known with typical motor impairment. Besides motor symptoms, non-motor symptoms (NMS) occur very frequently among patients with IPD. This study aims to assess the presence of non-motor symptoms with the severity of motor symptoms.Materials and Methods: Alaaddin Keykubat University Training and Research Hospital’s database has been screened for identifying patients with IPD from 2015-2019. The patients’ motor symptom, NMS, and Hoehn & Yahr stage (H&Y stage) were assessed with the Movement Disorder Society - Unified Parkinson’s Disease Rating Scale (MDS-UPDRS).Results: A total of 50 IPD patients were analyzed. Analysis by NMS part of MDS-UPDRS (Part I) showed that NMS was present in 99.7% of patients. NMS part score was positively correlated with H&Y stages and total motor scores of MDS-UPDRS (part II-III). The most common symptoms were pain (84%), daytime sleepiness (78%), and urinary problems (76%). Significantly, there was an association between motor impairment, H&Y, and the following NMS items; hallucinations/psychosis, depressed mood, daytime sleepiness, urinary problems, constipation, light-headedness on standing, and fatigue (p